The Development of the University of Priština from 1969 to 1974 Based on the Writings of the Student Newspaper "Novi Svet" - Miketić, Uroš D. (Collection of Papers of the Faculty of Philosophy in Priština, 2024)
The development of higher education in Kosovo began in 1958, with the University of Priština officially established in November 1969. Until that time, both teachers and students worked and lived under challenging conditions. By 1974, some improvements had been initiated, though issues persisted. Student accommodation remained insufficient, with dormitories offering too few rooms. Although private housing had certain advantages, students expressed dissatisfaction with overcrowding in the canteen, the poor quality of food, and unhygienic conditions. The difficult economic conditions in Kosovo affected students’ living standards and academic success. Over 8,000 students were provided with loans or scholarships. The University commenced operations amid nationwide university reforms, yet these reforms produced mixed results locally. Political influence and other factors hindered full implementation. The University lacked the capacity to deliver high-quality services, as the student population grew at a disproportionately faster rate than the teaching staff and campus facilities. Additional challenges included insufficient library resources and textbooks, an overloaded curriculum, outdated academic programs, and an inadequate assessment system. In terms of extracurricular activities, the University supported sports teams and sought to make physical education a compulsory subject. Students were active in the Ferial Association, cultural and artistic societies, and various local organizations. The student cooperative provided opportunities to earn income, yet cultural and social life remained limited. Basic healthcare services were available through the student polyclinic.